Peliosanthes thachii (Asparagaceae), a new species from Vietnam - Luu, Hong Truong; Nguyen, Hieu Cuong; Nao, Duy Phap; Nguyen, Tran Quoc Trung; Nguyen-Le, Xuan Bach (Phytotaxa, 2024)
Peliosanthes thachii is described and illustrated as a new species endemic to southern Vietnam. This is the fifth species found for the Neolourya group as it has a slender tortuous style with the stigma positioned above the level of anthers and an inferior ovary. The new species is morphologically closest to P. curviandra but it is distinguishable from all the others of the group by having smaller dimension leaves and floral parts, spherical and hardly open perianth, short and strongly tortous style and purple ovules. The data on phenology, distribution, and provisional assessment of conservation status of the new taxon are provided.